2012
DOI: 10.1159/000341935
|View full text |Cite
|
Sign up to set email alerts
|

Shared Copy Number Variation in Simultaneous Nephroblastoma and Neuroblastoma due to Fanconi Anemia

Abstract: Concurrent emergence of nephroblastoma (Wilms Tumor; WT) and neuroblastoma (NB) is rare and mostly observed in patients with severe subtypes of Fanconi anemia (FA) with or without VACTER-L association (VL). We investigated the hypothesis that early consequences of genomic instability result in shared regions with copy number variation in different precursor cells that originate distinct embryonal tumors. We observed a newborn girl with FA and VL (aplasia of the thumbs, cloacal atresia (urogenital sinus), tethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Autosomal recessive inheritance of genes associated with cancer risk, including BRCA2, PALB2, and BLM, which cause chromosomal breakage syndromes, are also associated with an increased risk for WT (Md Zin et al 2011;Serra et al 2012). Each of these genes is associated with other clinical features and risks when inherited in a recessive manner.…”
Section: Wilms Tumor (Wt)mentioning
confidence: 99%
“…Autosomal recessive inheritance of genes associated with cancer risk, including BRCA2, PALB2, and BLM, which cause chromosomal breakage syndromes, are also associated with an increased risk for WT (Md Zin et al 2011;Serra et al 2012). Each of these genes is associated with other clinical features and risks when inherited in a recessive manner.…”
Section: Wilms Tumor (Wt)mentioning
confidence: 99%
“…These observations highlight a critical role for the HR pathway in protecting against cellular transformation, particularly of hormone-responsive, epithelial cells that have a high proliferative capacity. Interestingly, however, it has been shown that biallelic, null germline mutations in BRCA2 [ 10 14 ] and PALB2 [ 15 17 ], hypomorphic mutations in BRCA1 [ 18 , 19 ] and Rad51C [ 20 ], or in the case of RAD51 [ 21 ] a dominant mutation, all give rise to a spectrum of clinical symptoms that have features of Fanconi Anaemia (FA). Unlike Fanconi anaemia patients with mutations of one of the core complex Fanconi proteins, those with inherited mutations in the HR machinery, including PALB2 mutant patients, typically display severe developmental abnormalities, such as microcephaly, growth retardation, intellectual impairment as well as skeletal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“… 5 10% of patients with FA have at least three of the component parts of the VACTERL‐H association. 6 FA is a recessive autosomal condition involving bone marrow failure, congenital malformations (skeletal defects, especially radial ray aplasia, small stature, renal and genital malformations, microcephaly with microstomia, and microphthalmia), and a predisposition to malignancy.…”
Section: Discussionmentioning
confidence: 99%